2020
DOI: 10.1371/journal.pone.0230681
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychological functioning in postmenopausal women undergoing aromatase inhibitor treatment for early breast cancer

Abstract: Introduction Aromatase inhibitors (AIs) dramatically increased breast cancer (BC) survival, leading to enhanced attention to their long-term consequences on psychological functioning. Conflicting data has been examined regarding the association between AIs administration and the clinical psychological features in BC survivors (BCSs). Purpose As psychological symptoms often occur in such chronic diseases, our study aimed at exploring anxious and depressive symptoms and the perceived quality of life (QoL) in BCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 82 publications
1
39
1
Order By: Relevance
“…Interestingly, similar findings were shown in recent studies concerning the key role of defense mechanisms and related psychological functions in chronic illness ( Di Giuseppe et al, 2018 , 2019b , 2020b ; Catalano et al, 2019 ; Conversano, 2019 ; Merlo, 2019 ; Marchi et al, 2019 ; Lenzo et al, 2020 ; Martino et al, 2019a , b , 2020a ). In particular, mood disorders seem to negatively affect physical and psychological response to treatment in chronic patients ( Marazziti et al, 2008 ; Mula et al, 2008 ; Dell’Osso et al, 2012 ; Piccinni et al, 2012 ; Veltri et al, 2012 ; Martino et al, 2019c , 2020b ). Recent studies demonstrated that mindfulness disposition is related to anxiety and depression and this is observable among different clinical populations ( Idusohan-Moizer et al, 2015 ; Zhang et al, 2015 ; Lam et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, similar findings were shown in recent studies concerning the key role of defense mechanisms and related psychological functions in chronic illness ( Di Giuseppe et al, 2018 , 2019b , 2020b ; Catalano et al, 2019 ; Conversano, 2019 ; Merlo, 2019 ; Marchi et al, 2019 ; Lenzo et al, 2020 ; Martino et al, 2019a , b , 2020a ). In particular, mood disorders seem to negatively affect physical and psychological response to treatment in chronic patients ( Marazziti et al, 2008 ; Mula et al, 2008 ; Dell’Osso et al, 2012 ; Piccinni et al, 2012 ; Veltri et al, 2012 ; Martino et al, 2019c , 2020b ). Recent studies demonstrated that mindfulness disposition is related to anxiety and depression and this is observable among different clinical populations ( Idusohan-Moizer et al, 2015 ; Zhang et al, 2015 ; Lam et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness is a theoretical instance that finds its implementation in a set of meditation and psycho educational exercises aimed at understanding certain fundamental themes such as stress, attachment and dependence on internal and external content and therefore the importance of subjective observation of thoughts, emotions, and physical sensations (Kabat-Zinn, 2009 ; Rosa et al, 2019 ). Mindfulness propensity is known as facilitators of well-being and adaptation for healthcare professionals, together with high adaptive defense mechanisms (Catalano et al, 2019 ; Di Giuseppe et al, 2019a , 2020a , c ; Martino et al, 2020a ). Moreover, mindfulness interventions proved to be very helpful in reducing the psychopathological symptomatology of chronic conditions (Bonadonna, 2003 ; Catalano et al, 2017 ; Poli et al, 2017 , 2019 ; Conversano and Marchi, 2018 ; Marchini et al, 2018 ; Conversano, 2019 ; Di Giuseppe et al, 2019b , 2020b ; Martino et al, 2019a , b , 2020b ; Merlo, 2019 ; Conversano et al, 2020a ; Lenzo et al, 2020 ; Poli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…T2DM is a common chronic illness and it is considered a major health concern due to its prevalence and outcomes. T2DM may involve a serious impact on both morbidity and mortality, compromising individuals' health and perceived quality of life and provoking a very thoughtful social burden to society (Perry et al, 2015 ; Craparo et al, 2016 ; Catalano et al, 2019 ; Conversano, 2019 ; Di Giuseppe et al, 2019 , 2020 ; Martino et al, 2019c , 2020b ; Merlo, 2019 ; Zimmerman et al, 2019 ; Lenzo et al, 2020 ). T2DM is a pandemic chronic metabolic disease, due to insulin deficit and resistance, which affects more than 280 million people worldwide and within the next decade it is expected that more than 430 million people will suffer T2DM (American Diabetes Association, 2018 ).…”
Section: Introductionmentioning
confidence: 99%